The Influence of Human Resource Competence, Product Innovation, and Leadership on the Improvement of MSMEs (Fashion Sector) in Jambi City with Entrepreneurship Orientation as an Intervening Variable - Sri Rezeki Rahayu; Fitriaty; Musnaini (Citakonsultindo, 2025)
This quantitative study aims to analyse the influence of human resource competence, product innovation, and leadership on the improvement of fashion MSMEs in Jambi City, with entrepreneurial orientation as a mediating variable. Using 130 respondents analysed with the Partial Least Square (PLS) method, the results of the study show that HR competence, product innovation, leadership, and entrepreneurial orientation do not directly have a significant effect on MSME Improvement, indicating that these factors have not been strategically integrated into business operations. Another important finding is that Leadership has a positive and significant effect on Entrepreneurial Orientation, but Entrepreneurial Orientation is unable to mediate the relationship between other independent variables and MSME Improvement. This conclusion emphasises the need to strengthen managerial capacity and develop a more adaptive entrepreneurial mindset among fashion MSMEs in Jambi City so that entrepreneurial orientation can be transformed into a driver of real performance improvement. Keywords: Human Resource Competence, Product Innovation, Leadership, Entrepreneurial Orientation, SME Improvement